Cenários prospectivos: a inserção internacional de Uberlândia-MG, o maior polo atacadista distribuidor da América Latina. - Oliveira, Rodrigo Freitas de (2017)
This master's dissertation presents the construction of a prospective scenario on the international insertion of the municipality of Uberlândia, state of Minas Gerais, Brazil, known as the largest wholesale hub in Latin America. The ongoing development of International Relations can portray a new global perspective, especially when taking into account the context of Globalization and Complex Interdependence, which have profoundly changed the international environment, recognizing the possibility of international action by actors other than the State. Among them are the subnational actors, who increasingly seek to be part of the international environment. Panayotes Soldatos, while studying the development of these actors’ international performance, coined the term paradiplomacy, which refers to the extroversion process of subnational actors, such as local and regional governments, international organizations and transnational corporations that negotiate and practice agreements in specific areas. As to the international insertion of cities, Soldatos proposes a series of questions that need to be answered in order for a city to be considered international. The prospective scenario demonstrates that Uberlândia-MG has advanced in this process with the work that has been done over the last few years through the articulation of the city’s Internationalization Committee, the proximity with the municipal and state public powers and active participation of the private and academic sectors. However, the city still has a long way to go in order to meet the requirements proposed by Soldatos and achieve active internationalization as city-actor, through multilevel governance seeking the involvement of various actors in different levels, both horizontally as well as vertically, combining the federal, state and municipal public powers, with emphasis to the presence of the federal government at the local level, in accordance with the ideas of the State’s new spaces. As to the role of the local wholesale distribution sector, it is evident that even if it fulfills its role, this will not be enough for Uberlândia-MG to reach internationalization. However, it is important to emphasize that without its participation, the path for the city to reach ample internationalization will be much more difficult.